Ordinance No. 97, §§ 1-4, Town Council of Stanwood (1918) (Stanwood, Washington). - (:unkn) unknown (My University, 1917)
it shall be unlawful for any person, firm or corporation to sell, give or permit to be sold or given to any person under the age of eighteen (18) years any revolver, pistol or toy-pistol within the town of Stanwood.
Keywords: TRANSFER - MINORS